Development of Interactive Media Based Learning on Project- Based Learning in Learning Ipas Class V SD Negeri 2 Karangharjo - Naqiyyah, Zahrotun; Widiyanti, Ifa Seftia Rakhma (Syntax Corporation Indonesia, 2024)
This study aims to develop an interactive learning media based on Project Based Learning (PjBL) in the teaching of Natural and Social Sciences (IPAS) for fifth-grade students at SDN Karangharjo II. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The analysis phase was conducted to identify the needs and characteristics of the students. The media design was created based on the analysis results and followed by the development phase, which involved creating a prototype of the interactive media. Implementation was carried out through limited trials and revisions based on the feedback received. Evaluation was conducted to assess the effectiveness of the interactive learning media through learning outcomes tests and student satisfaction questionnaires. The results showed that the interactive learning media based on PjBL could increase students' interest and motivation to learn. Students were more actively engaged in the learning process and were able to practically apply the concepts of IPAS. Based on the evaluation results, the developed media received high scores in terms of usability, effectiveness, and student satisfaction. Therefore, the interactive learning media based on PjBL is effective for use in the teaching of IPAS for fifth-grade students at SDN Karangharjo II. This study recommends the widespread use of this media and further development to add more innovative interactive features.